Optometric low vision rehabilitation practice in Norway - public health care - Helland, Bodil; Sundling, Vibeke (Scandinavian Journal of Optometry and Visual Science, 2015)
The purpose was to describe the patient characteristics, the prescribing trends and habits among the public health care optometrists who perform low vision rehabilitation in Norway. Data were collected using a questionnaire to gather background details of the optometrist, and a practice registration form to register patient characteristics and information about the low vision device(s) prescribed. Both forms were distributed to 44 public health care optometrists. A total of 30 questionnaires and 20 practice registration forms were returned. This included data for 147 patients with visual impairment. Moderate to severe visual impairment according to The World Health Organization (WHO)’s definition (visual acuity ≤ 6/18) was present in 82 (59%) of the patients. Three out of four (75%) patients did not have sufficient vision for reading. Distance visual acuity was improved with best optical correction in 39 (28%) of the patients compared to the presenting visual acuity. The most frequently prescribed optical devices for near and distance vision were hand magnifiers and filters/tinted lenses respectively. Optometrists play an important role in vision rehabilitation of older people attending the low vision services. A number of the patients seen in low vision services are referred from non-eye care professionals and achieve improved vision with appropriate optical correction. Others are only mildly visually impaired with adequate optical correction alone. This indicates a potential to use general optometric practice as the first step for vision rehabilitation, as a number of people are only mildly visually impaired with adequate optical correction.